Improvement of Nutritional Quality of Tuber Flour as Local Food Resource (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Tuber plants are sources of carbohydrates which could be used as strategic national food reserves. Beside high carbohydrates, tubers also contain a number of bioactive compounds which have physiological effects as antioxidants. This research aimed to develop tuber flour products and increase additional value through the use of appropriate technology and diversification of processed products. Research samples were 16 tuber species. The method was crystallisation by utilization of blower system to accelerate the process of water content reduction. The data were analyzed using proximat analysis. Water content was 5.61-15%, ash content was 0.4-5.31%, carbohydrate content was 82-88%, protein content was 0.67-6.32%, and fat content was 1-7%. The result showed that chemical content of Suweg flour with pragelatinization method at 70ÂºC for 60 minutes had the highest water, ash, and fiber content which were 5.79%, 2.49%, and 43.73%, respectively. Meanwhile, the highest carbohydrate content obtained by heating for 10 minutes was 25.80%. Tubers flour is worthy to be used as raw materials for food industry.